School restorative justice, restorative discipline rather than punishment: a systematic review - Julio-Raul Cantera-Rios; Neptali Zegarra-Salazar; Juan Mendez-Vergaray; Edward Flores (Institute of Advanced Engineering and Science, 2024)
Restorative justice has become another alternative to do justice in society and its application is spreading outside the criminal field, although there are currently global proposals to apply it as restorative practices in the educational field with interesting results in relationships of coexistence, discipline, and confronting school violence, which impacts on the learning outcomes of students. The objective of this paper is to analyze the conditions of school discipline before the implementation of restorative practice strategies and the impact of their application as an alternative of damage restoration rather than punishment. The PRISMA methodology and the consultations of “Justice AND Restorative AND School” were carried out; also “Practices AND Restorative AND Students”; “Practices AND Restorative AND Violence”; “Justice AND Practices AND Restorative”, 30 articles published in Scopus and EBSCO carried out between 2018-2022 were considered. The studies showed significant benefits in the improvement of school discipline, reduction of suspensions, increased communication, respect, trust between students and teachers, among others; In this regard, the evidence continues to be limited and new studies are needed.